Comment in line 395:
[x₀ < S, so S - x₀ < 0; drop it]
Should be:
[x₀ < S, so S - x₀ > 0; drop it]
The proof is based on S - x₀ > 0, thus it's a typo of comment.
Fixes #68466
Change-Id: I68bb7cb909ba2bfe02a8873f74b57edc6679b72a
GitHub-Last-Rev:
40a2fc80cf22e97e0f535454a9b87b31b2e51421
GitHub-Pull-Request: golang/go#68487
Reviewed-on: https://go-review.googlesource.com/c/go/+/598855
Reviewed-by: Cherry Mui <cherryyz@google.com>
Reviewed-by: Keith Randall <khr@google.com>
LUCI-TryBot-Result: Go LUCI <golang-scoped@luci-project-accounts.iam.gserviceaccount.com>
Reviewed-by: Keith Randall <khr@golang.org>
Auto-Submit: Keith Randall <khr@golang.org>
≥ (1/y)·((x₁ - y₁ + 1)·S - x) [above: q̂·y₁ ≥ x₁ - y₁ + 1]
= (1/y)·(x₁·S - y₁·S + S - x) [distribute S]
= (1/y)·(S - x₀ - y₁·S) [-x = -x₁·S - x₀]
- > -y₁·S / y [x₀ < S, so S - x₀ < 0; drop it]
+ > -y₁·S / y [x₀ < S, so S - x₀ > 0; drop it]
≥ -1 [y₁·S ≤ y]
So q̂ - q > -1.